Guest Editorial: Special Section on Parallel and Distributed Computing Techniques for Non-Von Neumann Technologies - Pakin, Scott; Teuscher, Christof; Schuman, Catherine (IEEE transactions on parallel and distributed systems, 2022)
The title of this special section, Parallel and Distributed Computing Techniques for Non-Von Neumann Technologies, is a bit misleading. Technically, parallel and distributed computers already diverge from the basic architecture that John von Neumann proposed in 1945, although they are still based on processors that execute a sequence of instructions, each of which performs a simple action such as computing an arithmetic result, reading or writing memory, or branching to a new location in the instruction sequence. But what would a computer that is not based on this model of execution look like? The technologies discussed in the following articles are more exotic, more innovative, and more intriguing than what you are likely to encounter in a typical collection of peer reviewed computer-science articles. We hope that these articles will help you view computing in a new light and give you a sense of what the future of computing may look like.